Using the World Health Organization's Disability Assessment Schedule (2) to assess disability in community-dwelling stroke patients - Ayorinde I. Arowoiya; Toughieda Elloker; Farahana Karachi; Nondwe Mlenzana; Lee-Ann; Anthea Rhoda (AOSIS, 2017)
Background: Measurement of the extent of disability post-stroke is important to determine the impact of disability on these individuals and the effectiveness of interventions aimed at reducing the impact of their disability. Instruments used to measure disability should, however, be culturally sensitive. Objective: The aim of this study was to conduct a disability assessment using the World Health Organization's Disability Assessment Schedule 2.0 (WHODAS). Methods: A cross-sectional design was used. The study population included a conveniently selected 226 stroke patients living within community settings. These patients were followed up 6-12 months following the onset of the stroke and are currently residing in the community. Disability was measured using the WHODAS 2.0 and the data were analysed using descriptive and inferential statistics in Statistical Package for Social Sciences (SPSS). The WHODAS 2.0 enabled the assessment of disability within the domains of cognition, mobility, self-care, getting along with others, household activities, work activities and participation. Ethical clearance for the study was obtained from the University of the Western Cape. Results: In this sample, the domain mostly affected were household activities, with 38% having extreme difficulty with conducting these activities. This was followed by mobility (27%) and self-care (25%) being the domains that participants also had extreme difficulty with. Getting along with others was the domain that most (51%) of the participants had no difficulty with. ANOVA one-way test showed no significant association of participation restrictions with demographics factors. Conclusion: Rehabilitation of patients with stroke should focus on the patient's ability to engage in household activities, mobility and self-care.